2007
DOI: 10.1016/j.eururo.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Mapping of Invasive Urinary Bladder Cancer in Animal Models Using Invisible Light

Abstract: Objectives-With conventional methodology, sentinel lymph node (SLN) mapping of invasive urinary bladder cancer is technically challenging. This study was performed to determine the utility of invisible, near-infrared fluorescent (NIRF) light for patient-specific SLN mapping, in real time under complete image guidance.Methods-Lymphatic tracers, injection volume, NIRF excitation fluence rate, light collection of emitted fluorescence, and degree of bladder distension were systematically optimized in normal dogs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…In contrast, patent blue dyes bind to interstitial albumin and are taken up by local lymphatic tissue 17 . The efficiency with which the lymphatics are converted to bright blue channels by the vital dyes reflects their smaller hydrodynamic diameter, their ability to disperse quickly and even their capacity to readily progress through and beyond the sentinel nodes 15,16,18 . The different properties of the nanocolloids and the vital dyes act synergistically in SLNB; injection of the radio-isotope between 2 and 24 hours before surgery optimises its localisation in the sentinel nodes and intra-operative injection of the vital dye directs the surgeon to the lymphatics that track to the sentinel node.…”
Section: Sentinel Node Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, patent blue dyes bind to interstitial albumin and are taken up by local lymphatic tissue 17 . The efficiency with which the lymphatics are converted to bright blue channels by the vital dyes reflects their smaller hydrodynamic diameter, their ability to disperse quickly and even their capacity to readily progress through and beyond the sentinel nodes 15,16,18 . The different properties of the nanocolloids and the vital dyes act synergistically in SLNB; injection of the radio-isotope between 2 and 24 hours before surgery optimises its localisation in the sentinel nodes and intra-operative injection of the vital dye directs the surgeon to the lymphatics that track to the sentinel node.…”
Section: Sentinel Node Methodologymentioning
confidence: 99%
“…For example, in primary cervical cancer, it has been suggested that for carefully selected cases, SLNB may impact positively on younger women who do not want their fertility affected by extensive lymphadenectomy 78 . In urinary tract cancers, vital dyes have shown potential in identifying the lymph nodes which drain the bladder 15 . Similarly, preliminary data in head and neck cancers, suggest that SLNB may limit the post operative morbidity associated with radical neck dissections 79 .…”
Section: Benefits Of Vital Dyesmentioning
confidence: 99%
“…The recently developed cadmium telluride (Cd/Te) QDs emit fluorescence in the red and near-infrared range, which is ideal for in vivo imaging to avoid tissue auto-fluorescence. In fact, it has been applied to map sentinel lymph nodes in animal cancer models (Kim et al, 2004;Parungo et al, 2005;Soltesz et al, 2005Soltesz et al, , 2006Hama et al, 2007;Knapp et al, 2007).…”
mentioning
confidence: 99%
“…For example, NIRF-guided sentinel lymph-node mapping techniques could be a promising way in the near future to evaluate lymphatic metastasis in humans. 61,62 In the previous section, we reviewed four imaging modalities (MRI, CT, PET/SPECT, and optical imaging) widely applied in both research and clinical fields. They have both strengths and weaknesses for in vivo imaging.…”
Section: +mentioning
confidence: 99%
“…Various positron-emitting isotopes have been used, including 18 F, 15 O, 13 N, 11 C, 14 O, 64 Gu, 62 Gu, 124 I, 76 Br, 82 Rb, and 68 Ga, and most isotopes are produced in a cyclotron. In particular, 18 C =20.38 minutes), and the reaction time for the incorporation of the isotope with the parent molecule also must be considered.…”
mentioning
confidence: 99%